ANALISIS TARIF PELAYANAN JASA PELABUHAN (STUDI KASUS PELABUHAN TANJUNG PERAK SURABAYA) - Putri, Indah Ayu Johanda; Harini, Novita Vindri (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the determination of service tariffs at Tanjung Perak Port using a Mixed Method approach. Data were collected through observations, perception surveys, and interviews. The results show that service tariffs are influenced by several factors, such as the type of service (e.g., loading/unloading, anchoring, storage), the volume and type of goods, and policies set by the port authority. The tariff components include loading/unloading, anchoring, storage, administration, and other charges. A comparison of tariffs with other nearby ports indicates that Tanjung Perak's tariffs can be more competitive depending on each port’s policies. According to the survey, 82.4% of service users were satisfied with the provided services, 76.6% felt the quality matched the price, and 64.7% considered the tariff details important. This study highlights that port service tariffs at Tanjung Perak significantly influence user satisfaction and the port's competitiveness.